People, Place and Partnership: Exploring Strategies to Revitalise Town Centres - Hospers, Gert-Jan (European Spatial Research and Policy, 2017)
More and more town centres in Western Europe are in decline, as indicated by growing shop vacancy rates in shopping streets. To turn the tide, decision makers look for revitalisation strategies. Are there any solutions? Making use of theoretical insights, empirical findings and anecdotal evidence from the Netherlands, we suggest that town centre revitalisation is a matter of connecting people, place and partnership. First, strategies should be based on an understanding of how customers (people) behave. Secondly, redesign of the physical environment (place) might be needed, since visitors prefer compact centres that are built on a human scale and known for a unique profile. Finally, close collaboration between a wide range of local stakeholders (partnership) is essential. We conclude that town centre revitalisation is possible, but takes a lot of energy and patience from the actors involved.